2008
DOI: 10.1080/09540120701487666
|View full text |Cite
|
Sign up to set email alerts
|

HIV patient insight on adhering to medication: a qualitative analysis

Abstract: Research on HIV medication adherence has relied mainly on quantitative methods. The objective of this study was to explore factors associated with adherence from the HIV-infected patient's perspective. Six focus groups were convened with treatment-experienced HIV-positive individuals. The discussions focused on issues that make it easy or difficult to adhere to HIV regimens. Thirty-five patients participated in the focus groups, which were conducted in Washington, D.C., and Los Angeles. The mean age was 48; 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 24 publications
0
30
2
Order By: Relevance
“…Consistent with the HIV treatment adherence literature, we posited that non-cannabis using individuals would experience negative effects of HIV symptoms, including ART side effects, and that these symptoms would contribute to decreased treatment adherence (Beusterien et al, 2008). This prediction was primarily based on the results of recent work, among mostly non-cannabis using HIV populations, showing generally poor adherence to HIV treatment (Chesney 2003;Solomon and Halkitis 2008).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Consistent with the HIV treatment adherence literature, we posited that non-cannabis using individuals would experience negative effects of HIV symptoms, including ART side effects, and that these symptoms would contribute to decreased treatment adherence (Beusterien et al, 2008). This prediction was primarily based on the results of recent work, among mostly non-cannabis using HIV populations, showing generally poor adherence to HIV treatment (Chesney 2003;Solomon and Halkitis 2008).…”
mentioning
confidence: 54%
“…Studies that have assessed adherence rates among individuals with HIV have found that between 14 and 35 % of individuals with HIV have trouble maintaining at least 80 % adherence to ART (Chesney 2003;Solomon & Halkitis, 2008), with viral suppression not achieved among 30-70 % of HIV positive individuals (Paterson et al, 2000;Low-Beer et al, 2000). The primary contributors to poor adherence among individuals with HIV include medication side effects (e.g., nausea), regimen complexity (e.g., number of pills), substance use (French et al, 2011;Friedman et al, 2009), and emotional factors (e.g., anxiety, depression) (Beusterien et al, 2008;Parienti et al, 2009).…”
mentioning
confidence: 99%
“…Thirty-three out of 39 studies reported that perceived adverse ARV reactions decreased adherence [12, 15–46], whilst six studies [4752] described no apparent relationship. Nineteen studies [12, 1527, 29, 32, 36, 44, 47] were conducted in high-income countries, eight [30, 31, 33, 34, 41, 42, 46, 49] in middle-income countries, and twelve [28, 35, 3740, 43, 45, 48, 5052] in low-income countries. (Countries—see Tables 1, 2).…”
Section: Resultsmentioning
confidence: 99%
“…Valuable data, especially in the qualitative section, were obtained in this study. Beusterien et al reported that focus groups were a valuable qualitative method for studying issues in socially marginalized groups [12].…”
Section: Discussionmentioning
confidence: 99%